2012
DOI: 10.1007/s12079-012-0165-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms underlying the fetal programming of adult disease

Abstract: Adverse events in utero can be critical in determining quality of life and overall health. It is estimated that up to 50 % of metabolic syndrome diseases can be linked to an adverse fetal environment. However, the mechanisms linking impaired fetal development to these adult diseases remain elusive. This review uncovers some of the molecular mechanisms underlying how normal physiology may be impaired in fetal and postnatal life due to maternal insults in pregnancy. By understanding the mechanisms, which include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 172 publications
0
29
0
1
Order By: Relevance
“…Physiological epigenetic processes act in cell-specific and temporally regulated manners to influence normal development, tissue formation, differentiation, and aging 10, 12, 13 . Epigenetics also plays a critical role in the fetal programming of adult disease 3, 69, 73, 74 .…”
Section: Influences Of Epigenetics On Embryonic Developmentmentioning
confidence: 99%
“…Physiological epigenetic processes act in cell-specific and temporally regulated manners to influence normal development, tissue formation, differentiation, and aging 10, 12, 13 . Epigenetics also plays a critical role in the fetal programming of adult disease 3, 69, 73, 74 .…”
Section: Influences Of Epigenetics On Embryonic Developmentmentioning
confidence: 99%
“…‘perinatal programming’) within adipocytes . Recent studies suggest that the programming response involves epigenetic and transcriptional changes, endoplasmic reticulum stress and/or reactive oxygen species .…”
Section: Characteristics Of the Participantsmentioning
confidence: 99%
“…Epigenetic alterations indicate modifications in DNA without changes in DNA sequence through DNA methylation, post-translational histone modifications, modification of nuclear receptors, and microRNAs. 32,33 Clinical studies that examine epigenetic modification and clinical outcomes in childhood are limited. An example of a recent study that applied epigenetic strategies to cardiovascular pathophysiology in the young was reported by Breton et al 34 These investigators measured DNA methylation of nitric oxide synthase (NOS) and identified an association of percent DNA methylation of NOS1 with carotid inima-media thickness in children.…”
Section: Birth Weight and Intrauterine Effects On Childhood Bpmentioning
confidence: 99%